UJI DIAGNOSTIK PLASMODIUM MALARIA MENGGUNAKAN METODE IMUNOKROMATOGRAFI DIPERBANDINGKAN DENGAN PEMERIKSAAN MIKROSKOPIS - Ima Arum L; Purwanto AP; Arfi S; Tetrawindu H; M Octora; Mulyanto Mulyanto; Surayah K; Amanukarti Amanukarti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
Microscopic examination is still a gold standard for malaria diagnostic tests. Immunochromatographic (IC) technique can be usedas an alternative examination. The aim is to compare the identification value of immunochromatographic method diagnostic test tomicroscopic examination of malaria in laboratory examination. Cross sectional diagnostic study approach was applied to those withsymptoms of: (1) fever (temperature > 38°C) or intermittent fever lasting for two days or more (2) cephalgia/myalgia, 604 sampleswere taken consecutively in January to July 2005 from primary health centres of Sukaraja and Keruak, as well as Clinic Nugraha atLombok Timur district , province of Nusa Tenggara Barat . From these samples, there were 37 samples with P.vivax, 45 samples with P.falciparum, 5 samples with mixed infection and 517 samples without Plasmodium sp. From IC examination, results were reserved for 36samples with P. vivax, 69 samples with P. falciparum, 5 samples with mixed infection and 503 samples without Plasmodium sp. Diagnostictest data analysis showed that the immunochromatographic test revealed 100% sensitivity, 96.7% specificity, 83.2% positive predictivevalue and 100% negative predictive value. It can be concluded that malaria IC test is reliable to be used as a routine malaria test.